Risk a user's guide - McChrystal, Stanley A. (New York City Portfolio, 2021)
Retired four-star general Stan McChrystal has lived a life associated with the deadly risks of combat. From his first day at West Point, to his years in Afghanistan, to his efforts helping business leaders navigate a global pandemic, McChrystal has seen how individuals and organizations fail to mitigate risk. Why? Because they focus on the probability of something happening instead of the interface by which it can be managed. In this new book, General McChrystal offers a battle-tested system for detecting and responding to risk. Instead of defining risk as a force to predict, McChrystal and coauthor Anna Butrico show that there are in fact ten dimensions of control we can adjust at any given time. By closely monitoring these controls, we can maintain a healthy Risk Immune System that allows us to effectively anticipate, identify, analyze, and act upon the ever-present possibility that things will not go as planned. Drawing on examples ranging from military history to the business world, and offering practical exercises to improve preparedness, McChrystal illustrates how these ten factors are always in effect, and how by considering them, individuals and organizations can exert mastery over every conceivable sort of risk that they might face. We may not be able to see the future, but with McChrystal's hard-won guidance, we can improve our resistance and build a strong defense against what we know-and what we don't"
Includes bibliographical references and index.
Keywords: Risk management